A Novel Stent Coated with Antibodies to Endoglin Inhibits Neointimal Formation of Porcine Coronary Arteries. (4th May 2014) - Cui, Song; Liu, Jing-Hua; Song, Xian-Tao; Ma, Guo-Lin; Du, Ben-Jun; Lv, Shu-Zheng; Meng, Li-Jun; Gao, Quan-Sheng; Li, Kefeng
Abstract : Endoglin/CD105 is an accessory protein of the transforming growth factor-β receptor system that plays a critical role in proliferation of endothelial cells and neovasculature. Here, we aimed to assess the effect of novel stents coated with antibodies to endoglin (ENDs) on coronary neointima formation. Thirty ENDs, thirty sirolimus-eluting stents (SESs), and thirty bare metal stents (BMSs) were randomly assigned and placed in the coronary arteries in 30 juvenile pigs. Histomorphometric analysis and scanning electron microscopy were performed after stent implantation. Our results showed that after 7 days, there was no difference in the neointimal area and percent area stenosis in ENDs compared with SMSs or BMSs. After 14 days, the neointima area and percent area stenosis in ENDs were markedly decreased than those in BMSs or SESs ( P < 0.05 ) . Moreover, the percentage of reendothelialization was significantly higher in ENDs than that in SESs or BMSs ( P < 0.01 ) at 7 and 14 days. The artery injury and the inflammation scores were similar in all groups at 7 and 14 days. In conclusion, our results demonstrated for the first time to our knowledge that endoglin antibody-coated stents can markedly reduce restenosis by enhancing reendothelialization in the porcine model and potentially offer a new approach to prevent restenosis.